1996
DOI: 10.1002/(sici)1097-4644(1996)25+<112::aid-jcb16>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a chemoprevention cohort from a population of women at high risk for breast cancer

Abstract: In a prospective pilot study, we performed breast fine needle aspirations (FNAs) on 21 3 high-risk and 30 low-risk women and analyzed these aspirates for cytologic changes and biomarker abnormalities of aneuploidy and overexpressed estrogen receptor (ER), epidermal growth factor receptor (ECFR), p53 and HER-2lneu. High-risk women were those with a first degree relative with breast cancer (73%), prior biopsy indicating premalignant breast disease (26%), a history of breast cancer (1 3%), or some multiple of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…There have been three previous follow-up studies of p53 protein accumulation in benign breast tissue in relation to risk of subsequent breast cancer: one showed no association between p53 protein accumulation and risk of breast cancer (20); another (42) suggested that p53, when evaluated as part of a group of biomarkers, might be associated with risk; and in a previous study based on a subset of the subjects included in the present report, we showed that p53 protein accumulation in benign breast tissue was associated with a 2.5-fold increase in the risk of subsequent breast cancer (28). However, the first two of these studies were small and adjusted for confounding either incompletely (42) or not at all (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been three previous follow-up studies of p53 protein accumulation in benign breast tissue in relation to risk of subsequent breast cancer: one showed no association between p53 protein accumulation and risk of breast cancer (20); another (42) suggested that p53, when evaluated as part of a group of biomarkers, might be associated with risk; and in a previous study based on a subset of the subjects included in the present report, we showed that p53 protein accumulation in benign breast tissue was associated with a 2.5-fold increase in the risk of subsequent breast cancer (28). However, the first two of these studies were small and adjusted for confounding either incompletely (42) or not at all (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, the first two of these studies were small and adjusted for confounding either incompletely (42) or not at all (20). Furthermore, all of these studies used immunohistochemistry to detect p53 protein accumulation, which may have resulted in underascertainment of p53 changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulation of p53, which typically indicates a loss of p53 function due to p53 mutation, is associated with increased risk of progression of early-stage, benign breast disease to breast cancer (21,22), and mutations that compromise p53 function are found in f50% of human cancers (23). p53 is up-regulated during cellular stress and induces expression of genes that control cell cycle progression and programmed cell death.…”
Section: Introductionmentioning
confidence: 99%
“…Carcinogenesis is hypothesized to be a multistep process resulting from the progressive accumulation of genetic damage. Although loss or mutation of specific tumor suppressor genes such as TP53 promotes mammary carcinogenesis (Fabian et al, 1996;Rohan et al, 1998), not all damaged epithelial cells progress to malignancy and many are thought to be eliminated by apoptosis (Thompson, 1995). Mammary gland homeostasis requires a coordinated balanced between proliferation and programmed cell death.…”
Section: Introductionmentioning
confidence: 99%